FAKTOR –FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK PERHOTELAN DI KOTA JAMBI - Azizah Azizah (Universitas Batanghari Jambi, 2012)
The aim of the research is to find out the number of room occupants, average tariff per room, and deflator PDRB that become the factors determining tax revenue of hotels in Jambi City. The research was a descriptive study. The methods of obtaining the data were observation and library research. The data were secondary data of time series. They were analyzed by using regression analysis. The results reveal that the number of hotel visitors staying and using hotel facilities with average payment and tariff per room has a significant influence on hotel tax revenue. On the other hand, deflator PDRB dies not have a significant influence on hotel tax revenue in Jambi City.Keyword : Revenue, Tax, Hotel